(NgIDRODINAMIKA OZER (B/s - (NfILATOW(B, (NnIKOLAJ nIKOLAEWI^s; (NdEMIN(B, (N`(B. (Nl(B.s ((NsANKT(B-(NpETERBURG (B:s (NnAUKA(B. (NsANKT(B-(NpETERBURG(B. (NOTD(B-(NNIE(B,s, 1991)
(NbIBLIOGR(B.: (NS(B. 185-195 (150 (NNAZW(B.)s
(Nan sssr(B, (NkAREL(B. (NNAU^(B. (NCENTR(B, (NoTD(B. (NWOD(B. (NPROBL(B.s
Keywords: (NoZERA (B- (NgIDRODINAMIKAs